Detection of infectious laryngotracheitis virus (Gallid herpesvirus-1) from clinically infected chickens in Egypt by different diagnostic methods - Magouz, A. (Iran J Vet Res, 2018)
Infectious laryngotracheitis (ILT) disease is an acute highly contagious viral disease leading to massive economic losses to the national poultry industry. This study aimed to identify the most accurate and rapid diagnostic methods to rescue layer poultry farms from intense outbreaks in Egypt. Fifty pathological specimens were collected and subjected to virus isolation (VI), histopathology, direct fluorescent antibody technique (FAT) and polymerase chain reaction (PCR). Egg inoculation revealed stunted growth and white pock lesions on chorioallantoic membranes (CAM) in 23 samples. Isolation and propagation of infectious laryngotracheitis virus (ILTV) in cell culture showed syncytia formation 5 days post infection in 20 inoculated samples. PCR resulted in successful amplification of a 647 bp fragment of the thymidine kinase (TK) gene in 25 field samples. Histopathological examination of inoculated CAM showed intranuclear inclusion bodies with infiltration of inflammatory cells. Direct FAT showed intra-cytoplasmic apple green reactions in 18 examined tracheal tissues. PCR has been shown to be more sensitive, accurate and rapid than VI, FAT and histopathological examination.